A música como recurso pedagógico no processo de ensino e aprendizagem no componente curricular de Ciências nos anos iniciais do Ensino Fundamental - Tavares, Marco Aurélio da Silva (2021)
The use of music as a pedagogical resource in the Early Years provides opportunities for a new playful approach in the classroom, enriching the teaching and learning process, and contributing to students' creativity, emotional, psychomotor, socialization and cognitive aspects. In view of this, music in the teaching of Science, in line with well-defined objectives, can contribute to the student's integral development, transforming common sense into scientific knowledge. For this, it is also necessary to value the culture in which the student is inserted, so that he can build knowledge through relationships with music. From the context presented, this research project aimed to investigate the perceptions of students enrolled in the 4th and 5th grade, in two schools of the Municipal Education Network, in the municipality of Umuarama - PR, as well as the teachers who work in the respective schools, in classes from 1st to 5th year of Elementary School I, regarding the use of music as a pedagogical resource in Science Teaching in the classroom. The methodology used for the constitution and analysis of data was the Textual Discursive Analysis (ATD) by Moraes and Galiazzi (2016), which aimed to qualitatively analyze textual and discursive information. In addition to the field research carried out through interviews, the work involved a survey and bibliographical and documental review, in the light of authors from Music Education and Science Education, who contributed to the reflection of the object of study and elaboration of the dissertation. Through the analyses, the relevance of music as a pedagogical resource in the teaching and learning process in Science teaching was found, and its importance in the student's development, as well as the motivation to learn, a greater and more active engagement of students. students in the classroom, and the feeling of a happier and more pleasant environment. Therefore, we see how much it is necessary to continue research and studies on the use of music as a pedagogical resource in the teaching of Science. In the final considerations, the results confronted between field research and bibliographic research are presented, for an effective dialogue between theory and practice, pointing out assumptions that corroborate the practices of the academic-scientific-school field